The Role of Internet of Things and Security Aspects in STEM Education - Valentina Terzieva; Malinka Ivanova; Edita Djambazova; Svetozar Ilchev (Information)
In the last decade, Science, Technology, Engineering, and Mathematics (STEM) education has rapidly evolved and increasingly makes use of innovative technologies. This paper aims to explore and analyze the research on integrating the Internet of Things (IoT) within STEM education and outline key aspects and emerging trends. A complete picture of the recent ten years is gained by gathering bibliometric data from the Scopus and Web of Science scientific databases. Two search queries combining IoT, STEM education, and security were submitted to extract relevant publications and obtain insight into the explored area. The manual content analysis of the study results and publications outlines several key roles of IoT in implementing STEM educational practices, which are conceptualized to reflect user viewpoints. Widespread IoT applications in STEM at different educational levels are discussed and summarized. The special focus on security aspects showed that they are underrepresented, evidenced by the small number of publications related to IoT in STEM education. The importance of including topics aimed at designing and implementing secure IoT applications in STEM-oriented curricula and courses is also discussed.